Unveiling Propaganda in National Anthems as a Teaching Tool in the EFL Classroom - Leva, Bernarda (Music with a Message: Words, Music and Propaganda 2, 2025)
It is essential that students who learn a foreign language become familiar with the history and culture of the country whose language they are studying. By incorporating national anthems into teaching English as a Foreign Language (EFL), teachers can enhance both language learning and cultural awareness and create a more enriching classroom experience for their students. Anthems, throughout history, have served as powerful tools for propaganda, making them an excellent resource for educating students about this aspect. In this chapter, we will show how national anthems “God Save the King” (the United Kingdom), “The Star-Spangled Banner” (the United States), “Das Deutschlandlied” or “The Song of the Germans” (Germany), and “Zdravljica” (Slovenia) can serve as educational tools for revealing propaganda and ideology, explicitly targeting intermediate to upper-intermediate level students. By analysing the lyrics and exploring their origins and significance, we will delve into the concept of propaganda embedded within each of them. We will take a close look at two remakes of the anthems, each of which hides propaganda messages in its own way. This will provide a few more ideas specifically designed for the EFL classroom, drawing inspiration from national anthems.